The efficacy and safety of complement C5a inhibitors for patients with severe COVID-19: a systematic review and meta-analysis. Issue 1 (2nd January 2023) - Tsai, Chi-Lun; Lai, Chih-Cheng; Chen, Ching-Yi; Lee, Ho-Sheng
ABSTRACT: Background: The clinical efficacy and safety of complement C5a inhibitors for patients with severe COVID-19 remains unclear. Methods: The PubMed, Embase, Cochrane Library, and ClinicalTrials.gov databases were searched from their inception to 27 September 2022. Only studies that assessed the usefulness of C5a inhibitors for the treatment of patients with severe COVID-19 patients were included. The primary outcome was the risk of 28-day mortality. Results: Six studies, including four randomized controlled trials (RCTs) and two non-RCTs, were included. The study group receiving C5a inhibitors had a significantly lower risk of mortality compared with the control group (23.6% [70/297] vs 39.2% [136/347]; odds ratio [OR], 0.53; 95% confidence interval [CI]: 0.37–0.76; P < 0.001), and no heterogeneity was detected ( I 2 = 0%; P = 0.58). Compared with control group, the study group was associated with a similar risk of serious adverse events (AEs) (OR, 0.84; 95% CI: 0.57–1.23; P 0 = 0.37), infection (OR, 1.46; 95% CI: 0.77–2.79; P = 0.25) and acute kidney injury (OR, 0.89; 95% CI: 0.54–1.46; P = 0.64). Conclusion: C5a inhibitors could help reduce the risk of mortality in patients with severe COVID-19 infection while being as safe as placebos. These findings support the promising role of C5a inhibitors in the treatment of severe COVID-19.